2011
DOI: 10.3109/15622975.2011.560279
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of motor coordination problems in ADHD identifies genes for brain and muscle function

Abstract: Objectives:Motor coordination problems are frequent in children with attention deficit/hyperactivity disorder (ADHD). We performed the first genome-wide association study to identify genes contributing to motor coordination problems, hypothesizing that the presence of such problems in children with ADHD may identify a sample of reduced genetic heterogeneity. Methods:Children with ADHD from the International Multicentre ADHD Genetic study (IMAGE) study were evaluated with the Parental Account of Children's Symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 58 publications
(16 reference statements)
2
24
1
Order By: Relevance
“…In light of these findings, one might ask if muscle release problems are involved in gross movements such as walking and running as well as in fine motor skills such as handwriting. Fliers et al [78] found an association between motor problems in ADHD and genes involved in muscles function.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these findings, one might ask if muscle release problems are involved in gross movements such as walking and running as well as in fine motor skills such as handwriting. Fliers et al [78] found an association between motor problems in ADHD and genes involved in muscles function.…”
Section: Discussionmentioning
confidence: 99%
“…The initial GWAS of ADHD [76][77][78][79][80][81][82][83][84][85][86] did not discover any DNA variants that achieved genome-wide significance, even when most of these samples were combined in metaanalysis having a sample size of 2064 trios (two parents and an ADHD child), 896 ADHD patients, and 2455 controls [87]. That study did find statistical significance for a group of candidate genes previously nominated by members of the International Multisite ADHD Genetics (IMAGE) project [88].…”
Section: Genome-wide Significant Common Variantsmentioning
confidence: 97%
“…It is possible that RLS is co-morbid with ADHD or that they share a common DAergic deficit. Also, ADHD separately and ADHD together with RLS have been found to be associated with sleep disorders such as insomnia and a common genetic polymorphism [79-81]. In a recent study, 64% of children with ADHD were estimated to suffer from RLS judged by their nocturnal periodic limb movement [82].…”
Section: Methodsmentioning
confidence: 99%